Pengaruh Kepemimpinan Yang Melayani Dan Karakteristik Pekerjaan Terhadap Kepuasan Kerja Karyawan - Fathillah Sugiarto, Nismaya; Suko Priyono, Bambang (Fakultas Ekonomi Universitas Gresik, 2023)
This study aimed to determine the influence of servant leadership and job characteristics on job satisfaction at PT Supralita Mandiri Semarang. The research method used in this research uses quantitative methods with a sample of 105 employees. The analysis used is multiple linear regression. The results of the study indicate a positive and significant influence of servant leadership on job satisfaction by showing a significant value of 0.000 <0.05. In the research results, the variable of job characteristics also shows a positive and significant influence on job satisfaction as evidenced by a significant value of 0.000 <0.05. The study results show that employee job satisfaction at PT Supralita Mandiri Semarang Branch is influenced by serving leadership and job characteristics with a percentage of 59.8%.